Is ICT Enabled Information Access Impacting the Productivity of selected Crops Uniformly? : A Case Study on North 24 Parganas of West Bengal (International Journal of Food and Nutritional Sciences, 2022)
Context: Despite the green revolution measures in mid-sixties we can find asymmetry across the states in India to get the benefit of that Green revolution at the country level. The states in eastern region of India are characterised by alluvial soils, a humid climate, low levels of irrigation (except in case of West Bengal), relatively high rainfall, and a population density. Agricultural Productivity can be defined as a ratio of the volume measure of output to the volume measure of input use. Agricultural yield is not only dependent on conventional input factors but also dependent on several environmental and market-led factors therefore agriculture extension along with the ICT (Information & Communication Technology) can disseminate demand-driven information to the farmers for their diverse information need in a cost-effective and efficient manner.